ANALISA PENGENDALIAN BIAYA DAN WAKTU PELAKSANAAN PADA PROYEK PEMBANGUNAN RUANG KELAS BARU MIN 5 MALUKU TENGAH DENGAN MENGGUNAKAN METODE NILAI HASIL - Cici Amanda Latuconsina; Saleh, La Mohammat; Gasperz, Willem (Journal Agregate, 2024)
In project implementation, there is often project completion that is not under planning both in terms of cost and time, so to overcome it requires good project management in the form of cost control and good implementation time in order to help the implementation as planned. in the MIN 5 Central Maluku New Classroom Construction Project located in Tulehu Village, Salahutu District, Central Maluku Regency which has a budget of Rp. 2,891,000,000.00 with a planned implementation time of 120 calendar days from June to October 2022 but the realization of the project is late and completed in 161 calendar days. To overcome these problems, the author uses the Result Value method.The Earned Value method is a control method used to control project costs and time in an integrated manner. Project time or schedule control is a process of monitoring the status of project activities to determine the progress or progress of the project. While project cost control is a process of monitoring the status of project costs to find out project costs at the time of the project.From the results of the analysis in the 3rd month, the value of the cost variance (CV) shows the number (-), which means that the cost of project expenses is greater than the budget. While the value (SV) of the schedule variant shows (-), which means the work is carried out later than the work. However, the evaluation in the 4th month seen from the value of the cost variance (CV) shows a number (+), which means that the cost of expenses is smaller than the budget (Rp.2,891,000,000,00) with the actual cost (ACWP) of the 4th month of (Rp.1,775,028,092.00). The profit obtained by the contractor amounted to (Rp.174,661,809). And the time required to complete the project is 5.53 months.